Efficacy of autologous platelet-rich plasma in treating patients with burn wounds: A protocol for systematic review and meta-analysis. Issue 17 (30th April 2021) - Wu, Yan-Hong; Zhang, Li-Ming; Wang, Yu-Zhi; Chen, Jian-Wu; Zhang, Bin; Tang, Jian-Bing; Cheng, Biao
Abstract: Background: Burns are still regarded among severe health problems related to high morbidity and mortality rates globally. In essence, health problems associated with burns can cause significant economic burden to society. Regardless of treatment available options, no best treatment was considered adequate for treating severe burns. In particular, only a few studies have focused on the effect of autologous platelet-rich plasma to treat burn wounds. The present study aim to systematically review existing literature to examine the effectiveness and safety of autologous platelet-rich plasma (PRP) to treat burn wounds. Methods: For this study, we will conduct a systematic search using MEDLINE, EMBASE, the Cochrane Library, Web of Science, CINAHL, as well as Scopus to discover randomised controlled trials (RCTs) for the examination of effectiveness and safety of autologous PRP to treat burn wounds from their inception to March 2021 with no language restrictions. Additionally, we will search Google Scholar, ClinicalTrials.gov, as well as the reference lists of studies considered in the research to ascertain possibly eligible studies. We used two independent authors to evaluate studies for inclusion and conduct data extraction. We intend to assess study bias and quality utilizing the Cochrane Collaboration's Risk of Bias Tool 2.0. Also, we will pool study results using the fixed-effects model or random-effects model. Finally, any disagreements emanating from the process will be addressed through discussion or using a third author to mediate situations leading to disagreement. Results: The study aims at assessing the effectiveness and safety of autologous PRP for treating burn wounds. Conclusion: The study will provide specific substantiation to assess autologous PRP's effectiveness and safety in treating patients with burn wounds. Ethics and dissemination: The study does not require ethical approval since no published studies are used in it. OSF registration number: March 29, 2021.osf.io/74z5u. (https://osf.io/74z5u/ )